ITC core list : basic documentation for trade information services in developing countries (ITC GenevaCH, 1982)
Annotated bibliography of basic documentation for trade information services in developing countries. Lists references materials, bibliographies, classifications, dictionaries, handbooks, directories, selected materials on product market information, country economic conditions, international trade statistics, materials on functional subjects related to trade promotion and export marketing. Gives bibliographical references, description of contents, periodicity, publishers' addresses and prices of publications.
IDS